(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the modern society, technology is everywhere. From birth, children learn about technology and develop computer competence. Whether a baby, preschooler, or adult – it doesn't matter, everyone has basic skills in manipulating devices and interacting with the Internet (according to age, body functionality, etc.). However, this is not what can satisfy the growing need to change approaches to professional activities in various fields of science and life. In particular, to education at all levels, which should ensure qualitative and quantitative changes for further professional activity. For example, we conducted a review of the latest theoretical and practical publications on the development and creation of online applications, which formed the basis for our own reflections on their implementation and use. It is not the first year that we have been addressing the issue of application development, collecting and analysing information on the involvement of future teachers in content development. After all, observing the development of technological solutions in developed countries of Europe and the USA, we analysed the development and demand for new technological solutions in education. And as a result of this introduction, based on the analysis, we were able to consider: fundamental differences in understanding and approaches to working with applications in the Ukrainian scientific community and in international practice; analyse the potential of developing and creating applications by students majoring in primary education and preschool education; to make a snapshot of data through feedback on their e-portfolios of relevant developments of their own production and lists of applications available online. This approach allowed us to draw conclusions about the potential risks of implementing online applications in practice. We also identified critical points in preparing teachers to use existing, create and develop their own online applications for working with children.